Research into operation efficiency of single-bucket hydraulic excavators - R. F. Salikhov; V. N. Kuznetsova; I. S. Kuznetsov (Вестник СибАДИ)
Introduction. The article presents the results of research of technical parameters reflecting the use of single-bucket hydraulic excavators by time. The dependencies given in normative documents necessary for processing of the obtained data are analyzed. The existing systems of data collection from the on-board computer of single-bucket excavator were analyzed. The excavator manufactured by Hitachi (Japan) was chosen as the machine under study.Methods and materials. To determine the utilization rates by time (excluding idling and movement within the object), idling, the data collection methodology was described. Excel and Statistica software was used to process the obtained database. The description of histograms formed with the help of on-board computer software was performed. A number of formulas allowing to estimate the efficiency of excavator operation without taking into account time losses for idling were proposed.Results. The obtained sample was processed with the help of Statistica software. Time utilization factor of single-bucket excavator is described by beta-distribution, idling factor by Weibull distribution. The parameters of distribution laws of time utilization and idling coefficients (mathematical expectation, Student’s coefficient) were also obtained. Numerical characteristics of the data samples were obtained according to the dependencies proposed by the authors. It was found that the average share of idling is 21% during the shift, and its duration is about 2 hours.Conclusion. The obtained values of the coefficients characterizing the intensity of operation can be used by operating enterprises in planning the rate of construction of facilities. It was concluded that the obtained data differ from the values described in normative documents, and their implementation will allow better planning of the process of work production.